Facing the giants [videorecording (DVD)] - Kendrick, Alex, 1970-; Blackwell, James; Cave, Bailey (Sony Pictures Home Entertainment, 2007)
A high school football coach with a history of losing games faces not only the pressures from a group of fathers wanting him fired, but also the possibility that his wife can never have children. When he turns to God, will his prayers be answered?